Dispersi Karbon Monoksida (CO) dari Emisi Transportasi Menggunakan Model Gaussian Line Source di Jalan Jendral Sudirman Pekanbaru - Aryo Sasmita; Imalatunil Khaira; Shinta Elystia; Muhammad Reza (Journal of Environmental Engineering and Waste Management, 2021)
Transportation is the most influential source in increasing levels of carbon monoxide (CO) in the air. Pekanbaru is the capital of Riau province which is experiencing rapid economic development that is a cause of population growth and increasing the number of motorized vehicles. The purpose of this study is to measure CO concentrations from mobile sources then compare them with PP No. 41 of 1999, calculating CO concentrations with the Gaussian Line Source Model, and mapping the predicted distribution of CO emissions on Jalan Jendral Sudirman, Pekanbaru City. The method used is counting the number of motorized vehicles (traffic counting) and measured the concentration of CO and wind speed in the field.  The results showed that the highest CO concentration on Jalan Jendral Sudirman Pekanbaru City was on Tuesday with a concentration of 6603.95 µg/m3 (5.767 PPM) at the sampling point in front of Ramayana Store and 1.4620.3 µg/m3 at the sampling point in front of Sudirman Square, both concentrations are still below the air quality standard based on PP No. 41 of 1999. From the calculation of the model, the concentration obtained in Ramayana for the measurement distance of 0 m was 27.198 µg/m3, at a distance of 5 m was 0.133 µg/m3, and at a distance of 10 m was 0.060 µg/m3. At Sudirman Square, obtained CO concentrations for the measurement of 0 m is 26.869 µg/m3, at a distance of 5 m is 0.131 µg/m3, at  a distance of 10 m is 0.059 µg/m3.